Analysis of the Behavior in the Wind Tunnel of an Experimental Model of Savonius with Interlocking Cups with the Classic Ones with 2, 3 and 4 Semi-Cylindrical Cups - Nelu CAZACU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2021)
The paper is based on experiments conducted on the wind tunnel at low wind speeds (<9.5 m/s), on an experimental model of S-rotor wind turbine type with four blades and a D/H ratio of 1. Semi-cylindrical cups opposite 180 degrees are aerodynamically coupled by overlap and with an air passage gap to equalize the pressures. The formed channel is shaped to allow the same for pairs of blades at 90 degrees. The experimental model has an area of 0.025 m2 which represents 10% of the surface of the measuring section of the wind tunnel (0.25 m2). The behavior of the experimental model was compared with the experimental models of S-rotor with 2, 3 and 4 semi-cylindrical cups, with the same interception surface. The results confirm the better start of the experimental model by reducing dead zones and operating more evenly and stably over a longer range of wind speeds. The results confirm the validity of the proposed concept of interwoven aerodynamic coupling of semi-cylindrical cups.